2008
DOI: 10.4049/jimmunol.180.6.3719
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Filamentous Bacteriophagefdto Deliver MAGE-A10 or MAGE-A3 HLA-A2-Restricted Peptides and to Induce Strong Antitumor CTL Responses

Abstract: Delivery of tumor-associated Ag-derived peptides in a high immunogenic form represents one of the key issues for effective peptide-based cancer vaccine development. We report herein the ability of nonpathogenic filamentous bacteriophage fd virions to deliver HLA-A2-restricted MAGE-A10254–262- or MAGE-A3271–279-derived peptides and to elicit potent specific CTL responses in vitro and in vivo. Interestingly, human anti-MAGE-A3271–279-specific CTLs were able to kill human MAGE-A3+ tumor cells, even if these cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 41 publications
3
46
0
Order By: Relevance
“…MAGE expression is not the exclusive property of melanoma cells; among other tumors, colon carcinoma cells naturally express MAGE. CEA-, MUC1-, and MAGE-expressor allogeneic colon carcinoma cells used as vaccines presented these antigens in an immunogenic manner and elicited anti-tumor CTL reactions [212,325,342]. It probably will be first in the colon where phages will prove themselves to be oncosuppresssive.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…MAGE expression is not the exclusive property of melanoma cells; among other tumors, colon carcinoma cells naturally express MAGE. CEA-, MUC1-, and MAGE-expressor allogeneic colon carcinoma cells used as vaccines presented these antigens in an immunogenic manner and elicited anti-tumor CTL reactions [212,325,342]. It probably will be first in the colon where phages will prove themselves to be oncosuppresssive.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Tumor size was assessed using caliper and recorded as tumor volume (mm 3 ) according to the formula (d 2 Â D)/2 where d and D are the shortest and the longest diameters. Mice were culled once tumor size met or exceeded 1500 mm 3 , in accordance with established guidelines.…”
Section: Analysis Of Ifn-a and Il-6 Productionmentioning
confidence: 99%
“…In this context we previously demonstrated that fd phage particles have access to both MHC class I and class II compartments [1] and that the antigenic determinants displayed by fd virions on the major pVIII coat protein trigger specific CTL responses [2,3]. However, the full potential of the fd bacteriophage system for vaccine formulation is still ameliorable by exploiting simultaneous display on different phage coat proteins.…”
Section: Introductionmentioning
confidence: 99%
“…15 Briefly, 2 ml of the FliTrx library was induced in the presence of IMC medium containing ampicillin and 100 lg/ml tryptophan at 25 C. Bacteria were then ''panned'' on 60-mm tissue culture plates (Becton Dickinson, Franklin Lakes, NJ) pretreated with the mAb under investigation (50 lg/ml in sterile water). After the removal of unbound cells, bacteria were amplified o/n in IMC medium at 25 C. After five rounds of panning and culture, E. coli were streaked onto RMG medium plates containing 100 lg/ml ampicillin and incubated overnight at 30 C. Individual clones tested positive in Western blot 7 were selected and amplified o/n at 30 C in RM medium containing ampicillin. DNA was isolated using the NucleoSpin kit (Macherey-Nagel, Oensingen, Switzerland), and plasmids were sequenced by using the FliTrx forward or Rsr reverse sequencing primers.…”
Section: Epitope Mappingmentioning
confidence: 99%
“…On the other hand, only a limited number of reagents are available to detect the corresponding proteins. 3 MAGE-A10 is probably the most immunogenic antigen of the MAGE-A family, [4][5][6][7][8] and, therefore, it represents a potentially highly attractive target of active specific immunotherapies. This antigen, expressed in the form of a 72-kDa nuclear protein, has been identified thanks to broadly reactive monoclonal antibodies (mAbs) recognizing it together with other members of the MAGE-A family.…”
mentioning
confidence: 99%